Penguatan Kapasitas Jaksa Melalui Koordinasi dalam Proses Penyidikan dan Penuntutan dalam RUU KUHAP: Studi Perbandingan Amerika Serikat, Belanda dan Indonesia - Sofian, Ahmad (Faculty of Law, Universitas Jambi, 2025)
This study discusses and critically evaluates the application of the principle of functional differentiation of investigation and prosecution and the principle of dominus litis in the Criminal Procedure Code and how it should be regulated in the future Criminal Procedure Code. This study uses a normative legal method with a comparative legal approach, namely comparing the application of investigation and prosecution in the United States and the Netherlands. The importance of this study is to analyze the differences between the stages of investigation and prosecution between Indonesia, the United States and Indonesia, so that it can emphasize whether the principle of functional differentiation of investigation must still be maintained in the R-KUHAP or eliminated, or maintained with improvements. The study aims to compare the application of investigation and prosecution in the United States and the Netherlands in the application of the principle of functional differentiation and relate it to the principle of dominus litis in the R-KUHAP. The research questions include: (1) How is the critical evaluation of the application of the principle of functional differentiation of investigation and prosecution in the Criminal Procedure Code? (2) How do investigations and prosecutions compare in the United States and the Netherlands? (3) How should investigation and prosecution be regulated in the R-KUHAP by linking it to the principle of dominus litis? This study concludes that the principle of functional differentiation in the KUHAP in practice experiences problems with limited coordination, the role of prosecutors is not optimal and has not fully realized prosecutors as dominus litis (case controllers) so that there are obstacles in several prosecution and evidence processes in court. When compared to the United States, prosecutors have a very strong role in determining whether a case will be continued to court or not. Meanwhile, in the Netherlands, the investigation function is held by the police and the prosecutor's office, law enforcement agencies are under one ministry, namely the Ministry of Justice, so that coordination between institutions is smoother. The principle of dominus litis places prosecutors as controllers of the case process from the investigation stage to the execution of the verdict. The R-KUHAP, by strengthening the role of prosecutors in investigation and prosecution, is expected to be able to realize this principle in the Indonesian criminal justice system. This study recommends: 1) The need for better coordination between investigators and public prosecutors; 2) Strengthening the role of prosecutors in investigations, but still paying attention to the principle of independence of investigations; 3) Clearer regulations regarding the time period for resolving cases; 4) The need for a change in legal culture among law enforcement officers to support the implementation of the R-KUHAP; 5) Encouraging a shift in the paradigm of law enforcement towards restorative justice. ABSTRAK Penerapan asas differensiasi fungsional penyidikan dan penuntutan di Indonesia ditandai dengan terbatasnya penerapan asas dominus litis. Studi ini membahas, membandingkan dan mengevaluasi secara kritis penerapan asas differensiasi fungsional penyidikan dan penuntutan dan asas dominus litis di Indonesia dalam KUHAP dan bagaimana sebaiknya pengaturan dalam KUHAP di masa depan. Studi ini menggunakan metode yuridis normatif dengan pendekatan perbandingan hukum yaitu membandingkan penerapan penyidikan dan penuntutan di Amerika Serikat (AS) dan Belanda. Pentingnya kajian ini dilakukan mengingat penerapan asas differensiasi fungsional di Indonesia yang cenderung membatasi Kejaksaan sebagai pengendali perkara. Studi ini bertujuan untuk membandingkan penerapan penyidikan dan penuntutan di AS dan Belanda dalam penerapan asas differensiasi fungsional dan mengaitkannya dengan asas dominus litis dalam R-KUHAP. Studi ini menyimpulkan, asas diferensiasi fungsional dalam KUHAP pada praktiknya membatasi peran jaksa sebagai dominus litis (pengendali perkara) sehingga mengalami hambatan dalam beberapa proses penuntutan dan pembuktian di pengadilan. Berbeda dengan Amerika Serikat, Jaksa memiliki peran yang sangat kuat dalam menentukan apakah suatu kasus akan dilanjutkan ke pengadilan atau tidak. Di Belanda, fungsi penyidikan dimiliki oleh kepolisian dan kejaksaan, lembaga-lembaga penegak hukum berada di bawah satu kementerian, yaitu Kementerian Kehakiman, sehingga koordinasi antar lembaga lebih lancar. Kajian ini merekomendasikan: 1) Perlunya koordinasi yang lebih baik antara penyidik dan penuntut umum; 2) Penguatan peran jaksa dalam penyidikan, namun tetap memperhatikan prinsip independensi penyidikan; 3) Pengaturan yang lebih jelas mengenai jangka waktu penyelesaian perkara; 4) Perlunya perubahan budaya hukum di kalangan aparat penegak hukum untuk mendukung penerapan R-KUHAP; 5) Mendorong pergeseran paradigma penegakan hukum ke arah keadilan restoratif.